The Optimal Approach for a Superior Hypogastric Plexus Block. Issue 3 (6th July 2017) - Choi, Ji Won; Kim, Won Ho; Lee, Chul Joong; Sim, Woo Seog; Park, Sukhee; Chae, Hyun Byung
Abstract: Introduction: Superior hypogastric plexus block (SHGPB) is technically difficult, and an accurate procedure is required to avoid potential complications. We attempted to determine the reference angles for fluoroscopy‐assisted SHGPB and to establish a predictor as a guide to select the optimal approach between the classic posterior approach and transdiscal approach. Methods: Abdominopelvic computed tomography (CT) scans from 268 patients diagnosed with pelvic malignancies were examined. The oblique and axial angles needed for the fluoroscope were measured both for posterior and transdiscal approaches by simulating the needle trajectory on CT imaging. We developed an SHGPB index defined by the ratio (%) of the interposterior iliac border distance to the L5 body transverse diameter, which represents the relative transverse diameter of the bony pelvis. We evaluated whether it can help select the optimal approach for the SHGPB between the posterior and transdiscal approaches. Results: Males had a significantly smaller angle than females (right oblique angle for posterior approach, males 14 [range 12 to 17] degrees vs. females 19 [range 16 to 23] degrees; P < 0.001). An SHGPB index of < 150 was an independent predictor for failure of the classic posterior approach (odds ratio 31.3, 95% confidence interval 5.1 to 104.7). Conclusions: The optimal right oblique angle of fluoroscopy for the posterior approach is 13° to 15° in males and 19° to 20° in females. The transdiscal approach may be favored over the posterior approach when the bony pelvis is narrow relative to the target vertebral body, which can be measured by the SHGPB index being < 150.